2020
DOI: 10.3390/ijerph17030685
|View full text |Cite
|
Sign up to set email alerts
|

Six-Step Model of Nature-Based Therapy Process

Abstract: Several studies have confirmed that the natural environment has psychophysiological healing effects. However, few studies have investigated the healing process involved in the effect of the natural environment. To date, no theoretical model on the nature-based therapy process has been clearly established. Thus, the aim of this study was to develop a theoretical model of the nature-based therapy process by analyzing individual empirical data. Research materials were 180 self-reported essays on “Forest Therapy E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…The final step was to have a chance to recover attention and have a positive change of mind through the process of setting priorities and possibilities of life, actions, and goals, including reflection on one’s life. Oh et al [ 70 ] revealed a six-step psychological mechanism that causes emotional and cognitive changes in nature-based healing processes. It reported that participants could focus entirely on themselves and look into their emotions and thoughts when they have a deep interaction with nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final step was to have a chance to recover attention and have a positive change of mind through the process of setting priorities and possibilities of life, actions, and goals, including reflection on one’s life. Oh et al [ 70 ] revealed a six-step psychological mechanism that causes emotional and cognitive changes in nature-based healing processes. It reported that participants could focus entirely on themselves and look into their emotions and thoughts when they have a deep interaction with nature.…”
Section: Discussionmentioning
confidence: 99%
“…Each theme was found according to the forest healing factors and health benefits. Themes were derived from participants’ language (e.g., most frequently mentioned word/phrase within a cluster of codes) and findings from previous studies [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, PO1 and PO2 focus on reducing anxiety (present), PO3 on the enhancement of self-esteem, PO4 on depression, PO5 on parenting stress, and PO6 on anxiety (future) reduction. The order of these POs was based on a report that revealed that individual changes through the use of forests occur in the order of body, emotion, cognition, and behavior [21], and a study that structured the hierarchy between outcome variables [10]. In other words, the therapeutic functions of the forest are expected to have an overall positive effect on physical health and negative emotions such as depression and anxiety, self-esteem, and stress [26,35].…”
Section: Performance Objectivesmentioning
confidence: 99%
“…Forests therapy is one of the most accessible methods, especially for people with low socioeconomic status, because the program utilizes currently existing and available urban forests [20]. Forests can promote positive changes through exposure to nature's healing factors, such as air, sound, and green trees and healing ingredients such as terpene compounds [21,22]. Moreover, forests are effective in stimulating the mothers' feelings of competence in parenting [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation